A Qualitative Review on Halal Tourism: NVivo Approach - Nadia Nurul Izza; Aam Slamet Rusydiana; Sherrindra Avedta (SMART Insight, 2021)
According to the Global Muslim Travel Index report, the market share of Muslim travelers is increasing. It is expected to increase to USD 220 billion by 2020 and is expected to increase by USD 80 billion to USD 300 billion by 2026. The Muslim consumer market has been recognized as another important segment for cross-sectoral businesses. With this increasing interest, researchers are starting to focus on halal tourism. This study aims to identify and map research related to the development of halal tourism in the world of research for the last 14 years, from 2009 to 2022. The method used is a qualitative analysis of secondary data in the form of metadata from 287 Scopus-indexed publications, then processed using NVivo software. 12 Plus. The results of the study show that the number of publications on the development of halal tourism continues to increase. From the results of the exploration and visualization review of the halal tourism pattern, it was found that there are 4 research lines related to this topic including satisfaction with halal tourism, the role of government policies in halal tourism, innovative business opportunities for the halal tourism industry, the Muslim tourism market sector and players in the halal tourism sector. In addition, this study found that the halal tourism management system was still poorly organized. Therefore, the contribution of this research is very important for tourism operators, managers, and marketers of tourism destinations who have direct and indirect leadership in improving the halal tourism management system.